Food insecurity among nursing students: A mixed methods study. Issue 4 (23rd May 2020) - Bydalek, Katheryn; Williams, Susan G.; Fruh, Sharon M.; Sims, Brook M.; McCardle, Jillian; Minchew, Leigh A.; Graves, Rebecca J.; Elkins, John Casey; Jones, Loretta; Sittig, Scott
Abstract: Background: College students are among 48.1 table million Americans who experience food insecurity, affecting aspects of daily living, health, and academic performance. This study sought to assess food security in nursing students to determine the prevalence and significance of this issue. Methods: A mixed‐methods descriptive design was utilized to collect and analyze data through an online survey of junior and senior undergraduate nursing students. Both qualitative and quantitative questions were related to personal experience with food insecurity. Results: Approximately 40% of students responded that they were Sometimes / Often worried that food would run out before the next income arrived. In addition, 52% of the participants Sometimes/Often could not afford an adequate amount of food, and 35% reported having a shortage of food. Conclusion: University leadership, College of Nursing administrators, and nursing faculty should be aware of food insecurity among their students and identify strategies to assess and decrease this issue.